An analysis of 170 glioma patients and systematic review to investigate the association between IDH-1 mutations and preoperative glioma-related epilepsy. (September 2016) - Yang, Yuan; Mao, Qing; Wang, Xiang; Liu, Yanhui; Mao, Yunhe; Zhou, Qiao; Luo, Jiewen
Highlights: IDH1 mutation is associated with glioma associated seizures (GAS). Sub-group analysis showed IDH1 mutation is related to GAS in WHO grade II/III gliomas. Meta-analysis confirmed the IDH1 mutaion is associated with GAS in low grade gliomas. Abstract: Seizure is a common presenting symptom of glioma, and many biomarkers have been suggested to be associated with preoperative seizure; however, the relationships between IDH (isocitrate dehydrogenase) mutations and glioma-related epilepsy only recently been studied. The authors aimed to examine the correlations between IDH mutations in glioma patients with preoperative seizures and tumor location. A series of 170 glioma samples were analyzed for IDH1 R132H mutations (amino acid change from arginine to histidine at codon 132) with immunohistochemistry (IHC) staining and for IDH mutations with direct DNA sequencing when the IHC results were negative. If either the IHC or direct DNA sequencing result was positive, the IDH status was defined as mutated. The results of the IDH mutation examinations were used to analyze the relationship between mutations and glioma-related epilepsy. The study population consisted of 64 (37.6%) World Health Organization (WHO) grade II gliomas, 58 (34.1%) grade III, and 48 (28.3%) grade IV gliomas. A total of 84 samples with IDH1 mutations were observed in our study, and 54 of these presented with seizures as the initial symptoms, whereas 28 of the patients with wild-type IDH status presented with seizures (p = 0.043 for the WHO grade II gliomas, p = 0.002 for the grade III gliomas and p = 0.942 for the grade IV gliomas, chi-squared tests). Among the WHO grade II and III gliomas, IDH1 mutations were significantly associated with preoperative seizures, but no significant relationship between IDH mutations and preoperative seizures was found with glioblastoma multiforme.